330 An End to Doctor's Handwriting in the Digital Age: Evaluating the Legibility of Operation Notes in Otolaryngology. (28th February 2022) - Bhojwani, D.; Javed, H.; Amala, C.; Hashmi, S.
Abstract: According to GMC Good Medical Practice, clinicians must record their work 'clearly, accurately and legibly'. Operation notes are no exception and have several key functions. They serve reminder of procedural events, communicate information to the wider team and may be used as evidence when there are complications or complaints. The aim of this audit was to evaluate the legibility of operation notes within the Otolaryngology department at Peterborough City Hospital. Handwritten operation notes were audited from 8 dates chosen at random over a 2-month period (n = 27). Multiple surgeons and a variety of operations were included. Parameters such as legibility of the surgeon's name, patient identification, date, name of procedure, events, findings, closure and post-op instructions were recorded. Only 11% of the operation notes were legible in all relevant parameters. The surgeon's name was either absent or not identifiable from the handwriting in 48%. Documentation of the procedure itself and post-op instructions was illegible in 18% and 29% of notes respectively. Illegibility of operation notes is ultimately a patient safety-issue. Not only does it contribute to confusion about what happened during the surgery but also leaves room for error in terms of post-operative care and follow up. The results of the audit were discussed as part of a departmental meeting to highlight the importance of readable operation notes and help foster a culture of good record keeping. A switch to computerised operation notes could ensure legibility and thus improve standards of patient care in the hospital.